Phospholipase C: underrated players in microbial infections - Singh, Vinayak; Rai, Rupal; Mathew, Bijina J.; Chourasia, Rashmi; Singh, Anirudh K.; Kumar, Awanish; Chaurasiya, Shivendra K. (Frontiers in Cellular and Infection Microbiology, 2023)
During bacterial infections, one or more virulence factors are required to support survival, growth and colonization of the pathogen within the host leading to the symptoms characteristic of the disease. Outcome of bacterial infections is determined by several factors from both host as well as pathogen origin. Proteins and enzymes involved in cellular signaling are important players in determining the outcome of host pathogen interactions. Phospholipase C (PLC) participate in cellular signaling and regulation by virtue of their ability to hydrolyze membrane phospholipids into di-acyl-glycerol and inositol tri-phosphate, which further cause the activation of other signaling pathways involved in various processes including immune response. 13 PLC isoforms are known so far differing in their structure, regulation and tissue specific distribution. Different PLC isoforms have been implicated in various diseases including cancer and infectious diseases, however, their roles in infectious diseases are not understood clearly. Many studies have suggested prominent roles of both host as well as pathogen derived PLCs during infections. PLCs have also been shown to contribute towards disease pathogenesis and onset of disease symptoms. In this review, we have discussed the contribution of PLCs as determinant of outcome of host pathogen interaction and pathogenesis during bacterial infections of human importance.